'Informed consent' in consensual child welfare: some reflections on its controversial nature. Issue 5 (3rd September 2021) - Enroos, Rosi; Korpinen, Johanna; Pösö, Tarja
ABSTRACT: The article examines the nature of consent in the context of Finnish care order decision-making as described by social workers, parents and young people, all personally involved in care order decision-making, albeit in different roles: on the one hand, an authority asking for the view about a child removal, and on the other, a party expressing a view which has huge legal, social and moral implications for their family relations. Based on qualitative data, the analysis examines two criteria for informed consent: adequate information and freedom from undue influence. The findings highlight the messy and blurred nature of consent that is found in other fields of practice as well. There are, however, some distinctive features relevant to consensual services in child welfare which need to be further elaborated. In particular, family relationality shapes the nature of consent through intra-familial power and emotions, differently for parents and children. Critical awareness of the nature of consent is also important for an understanding of service-user participation and self-determination.